Scanning Electron Microscopy of Intact Colonies of Microorganisms - Whittaker, D. K. (1970)
Colonies of S. mutans OMZ61, Streptococcus sp. D182, Staphylococcus aureus Oxford NCTC 6571, and Candida albicans type A, MRL 3153 were grown on various media. Cubes of agar bearing two to three colonies were excised and processed for scanning electron microscopy. The characteristic shape of the colonies was seen when examined at low magnifications. At a magnification of 2,000 diameters, the arrangement of individual organisms within the colonies was observed. Plano-convex colonies consisted of uniformly distributed organisms, whereas S. mutans colonies presented a more complex arrangement possibly associated with the production of extracellular polysaccharides. Certain colonies were totally or partially covered by an adherent film through which the outline of the organisms could be distinguished.